Evaluasi Implementasi Enterprise Resources Planning pada Perusahaan Manufaktur dengan Model DeLone dan McLean - Albert Gozali; Johanes Supranto (Universitas Tarumanagara, 2020)
This research is intended to examine factors that influence the success of ERP implementation in winning competitive advantage. ERP is a device system that enables companies to manage efficiently and effectively the use of resources and provide integrated solutions for the company's information processing needs. DeLone & McLane success model was actively used since it was first introduced in 1992 and Measurement with the DeLone & McLean model is one of the most developed models to test the information success model. The sample of this study is the users of companies that use SAP as one of their information systems, several 200 people from various manufacturing companies to evaluate information systems based on user satisfaction. The results of the analysis show that all hypotheses show significant results obtained from positive values on the critical ratio (cr) and also the value of p values smaller than 5% (significant effect on α < 5%).